2004
DOI: 10.1093/bja/aeh032
|View full text |Cite
|
Sign up to set email alerts
|

Predicted values of propofol EC 50 and sevoflurane concentration for insertion of laryngeal mask Classic TM and ProSeal TM

Abstract: The estimated concentration of propofol and the sevoflurane concentration needed to allow insertion of the ProSeal are respectively 38 and 20% greater than those needed for insertion of the Classic LMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 19 publications
(11 reference statements)
4
48
2
Order By: Relevance
“…In our study, the concentration used to insert the LMA ™ and LT ™ without any patient's reaction could be considered as high when compared with a recent study that reported a Ce t of propofol for LMA ™ insertion around 3.14 Ϯ 0.33 µg mL Ϫ1 [25]. But in that previous study, the use of midazolam premedication and i.v.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, the concentration used to insert the LMA ™ and LT ™ without any patient's reaction could be considered as high when compared with a recent study that reported a Ce t of propofol for LMA ™ insertion around 3.14 Ϯ 0.33 µg mL Ϫ1 [25]. But in that previous study, the use of midazolam premedication and i.v.…”
Section: Discussioncontrasting
confidence: 57%
“…This study showed almost identical results to those that we reported earlier for Cp 50 of cLMA. Kodaka et al [14] reported that the Cp 50 of pLMA insertion was 4.32 F 0.67 lg/mL and was significantly higher than that of cLMA in same study. It showed that Cp 50 of pLMA in our study was significantly higher than that of a previous report (v 2 test, P b .05).…”
Section: Discussionmentioning
confidence: 51%
“…The differences that must be considered are that they used 2 mg intramuscular midazolam as premedication, whereas our study used no premedication. A size-3 LMA was used for all patients in their study, whereas our study used the size-4 LMA for patients weighing more than 50 kg [14].…”
Section: Discussionmentioning
confidence: 99%
“…6 INSERTION TECHNIQUE Insertion is recommended with head extended and lower neck flexed, and may be performed with or without an introducer.…”
Section: Depth Of Anesthesiamentioning
confidence: 99%